Determination of Optimum Harvesting Time for Periphyton Production on Artificial Substrates - Zaman, T; Alam, MMM (Progressive Agriculture, 2013)
The experiment was conducted in two cement made cisterns for a four-week period. Important physico-chemical water quality parameters and harvesting time in periphyton production were studied. During the study period, four groups of phytoplankton and two groups of zooplankton were observed. Among phytoplankton, Chlorophyceae was the most dominant having 62% Chlorella followed by Bacillariophyceae having 15% Navicula and 12% Cyclotella, Cyanophyceae having 5% Oscillatoria and 2% Anabaena and Euglenophyceae having 2% Euglena and 1% Phacus. The grand averages of periphyton mass production were 0.569 (± 0.242) mg DM/cm2 in C-1. There was highly significant (p<0.05) variation (F = 14.692) between C-1 and C-2 in respect of periphyton production. Cistern-1 was identified as more productive due to its favourable water quality parameters, i.e., water temperature of 24.6 to 28.3 ºC, Secchi disc reading of 18 to 33 cm, dissolved oxygen of 4.67 to 9.55 mg/L, pH of 9.12 to 10.18, NO3-N of 3.58 to 10.90 mg/L, NH3-N of 0.26 to 0.40 mg/L, PO4-P of 7.5 to 3.4 mg/L, conductivity 0.412 to 0.719 Ms. Third addition of substrate, that means 18- 19th day was identified as the optimum harvesting time of periphyton production. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16565 Progress. Agric. 23(1 & 2): 51 62, 2012